Answer:
B. y=3(x-1)2 + 3
Step-by-step explanation:
Given that
vertex of the parabola is at the point (1,3)
let's verify, if the option B is the correct equation of the parabola.
![y=3(x-1)^2 + 3\\ \\y=3(x^2+1-2x) + 3\\\\y=3x^2+3-6x + 3\\\\y=3x^2-6x + 6....Eq1](https://tex.z-dn.net/?f=y%3D3%28x-1%29%5E2%20%2B%203%5C%5C%20%5C%5Cy%3D3%28x%5E2%2B1-2x%29%20%2B%203%5C%5C%5C%5Cy%3D3x%5E2%2B3-6x%20%2B%203%5C%5C%5C%5Cy%3D3x%5E2-6x%20%2B%206....Eq1)
comparing to standard equationof parabola (standard quadratic equation), we get
![a=3, b=-6 and c=6](https://tex.z-dn.net/?f=a%3D3%2C%20b%3D-6%20and%20c%3D6)
to find the vertex we use formula for x- coordinate as ![x=-b/2a](https://tex.z-dn.net/?f=x%3D-b%2F2a)
![x=-(-6)/2(3)\\\\x=6/6\\x=1](https://tex.z-dn.net/?f=x%3D-%28-6%29%2F2%283%29%5C%5C%5C%5Cx%3D6%2F6%5C%5Cx%3D1)
to find y put x=1 in the Eq1, we get
![y=3(1)^2-6(1)+6\\\\y=3-6+6\\\\y=3](https://tex.z-dn.net/?f=y%3D3%281%29%5E2-6%281%29%2B6%5C%5C%5C%5Cy%3D3-6%2B6%5C%5C%5C%5Cy%3D3)
vertex =(x,y) = (1, 3)
thus vertex of the parabola from the equation y=3(x-1)2 + 3 is (1,3), thus verified
Answer:
Step-by-step explanation:
Divide 20.34 by 6 and you should get 3.39